1881 N.Y. Laws 103, § 412 - (:unkn) unknown (My University, 1881)
Tit. 12, § 412: Prohibited the concealed carrying of any kind of fire-arms, any sharp or dangerous weapon usually employed in attack or defense of the person. Violators guilty of a misdemeanor.
Keywords: CARRY - CONCEALED